ChemInform Abstract: Pd/C—Cu‐Mediated Direct and One‐Pot Synthesis of γ‐Ylidene Butenolides. Issue 31 (11th July 2013) - Rambabu, D.; Bhavani, S.; Nalivela, Kumara Swamy; Mukherjee, Soumita; Rao, M. V. Basaveswara; Pal, Manojit
Abstract It is found that the catalytic system efficiently promotes the coupling of iodoacrylic acid with terminal alkynes to form the target compounds with high regio‐ and stereoselectivity.